The mediating effects of inferences of manipulative intent between consumer skepticism and product judgement: a conceptual study - Tien, Cheryl (School of Marketing, Curtin Business School, 2010)
This paper proposes a research framework on the antecedents of consumers? skepticism toward advertising and its related outcome variables; including inferences of manipulative intent, attitudes toward the advertisement and product judgment. The scope of the study will be limited to the industry of beauty products, due to the myriad of dubious beauty ad claims. Consumer involvement and risk are also discussed as possible background variables for the framework. The paper will attempt to bridge a number of gaps inherent to consumer skepticism toward advertising, including validating the consumer susceptibly toward interpersonal influences scale and marketplace knowledge scale, in the context of mature target audiences and their degree of ad skepticism and empirically verify Obermiller and Spangenberg's (1998) suggestion of high skeptics infer high inferences of manipulative intent. The framework is built on the persuasion knowledge model and a conceptual model is used to explain the various relationships, leading to a series of hypotheses. This research provides implications for policy makers, strategists, advertisers and planners.